Stretching Reduces Skin Thickness and Improves Subcutaneous Tissue Mobility in a Murine Model of Systemic Sclerosis - Xiong, Ying; Berrueta, Lisbeth; Urso, Katia; Olenich, Sara; Muskaj, Igla; Badger, Gary J.; Aliprantis, Antonios; Lafyatis, Robert; Langevin, Helene M. (Frontiers in Immunology, 2017)
Objective Although physical therapy can help preserve mobility in patients with systemic sclerosis (SSc), stretching has not been used systematically as a treatment to prevent or reverse the disease process. We previously showed in rodent models that stretching promotes the resolution of connective tissue inflammation and reduces new collagen formation after injury. Here, we tested the hypothesis that stretching would impact scleroderma development using a mouse sclerodermatous graft-versus-host disease (sclGvHD) model. Methods The model consists in the adoptive transfer (allogeneic) of splenocytes from B10.D2 mice (graft) into Rag2−/− BALB/c hosts (sclGvHD), resulting in skin inflammation followed by fibrosis over 4 weeks. SclGvHD mice and controls were randomized to stretching in vivo for 10 min daily versus no stretching. Results Weekly ultrasound measurements of skin thickness and subcutaneous tissue mobility in the back (relative tissue displacement during passive trunk motion) successfully captured the different phases of the sclGvHD model. Stretching reduced skin thickness and increased subcutaneous tissue mobility compared to no stretching at week 3. Stretching also reduced the expression of CCL2 and ADAM8 in the skin at week 4, which are two genes known to be upregulated in both murine sclGvHD and the inflammatory subset of human SSc. However, there was no evidence that stretching attenuated inflammation at week 2. Conclusion Daily stretching for 10 min can improve skin thickness and mobility in the absence of any other treatment in the sclGvHD murine model. These pre-clinical results suggest that a systematic investigation of stretching as a therapeutic modality is warranted in patients with SSc.